Avaliação do desempenho, hematológica, bioquímica, parasitológica e histopatológica de bovinos de corte em sistema intensivo de produção - COSTA, Gustavo Lage (2010)
The profile of the Brazilian cattle industry has changed due to the search for more efficiency. It is transforming form extractive practices to new levels of intensification and productivity. In this context, the metabolic and parasitological profile of 39 crossbred animals, aged around 24 months at the time of entering the feedlot and prior to slaughter were performed, in order to assess the health of bovine finished in this breeding system. The following evaluations were carried out: hematology, biochemistry, histopathology and parasitology. The clinical biochemical evaluation consisted of the higidity assessment of the liver and kidney, comprising the balance of energy and protein of these animals. The parameters used were: ALP, AST, GGT, bilirubin (total, conjugated and unconjugated), total protein, albumin, globulin, urea, creatinine, cholesterol and triglycerides. Total proteins were fractionated by agarose gel electrophoresis. Parasitological assessment was done through EPG and stool culture. In histopathology fragments of liver, kidney, lynph nodes (mesenteric, pre scapular and pre femoral) and lung were observed. Alterations in biochemical and electrophoretic tests, suggestive of chronic liver disease, were found. Such alterations were noticed by the presence of foamy macrophages in the liver and mesenteric lymph nodes; however, these findings were not related to differences found in daily weight gain found. Histology did not show alterations suggestive of respiratory diseases.